Aspek Hukum Penyelesaian Sengketapenanaman Modal Melalui Mekanisme Alternative Dispute Resolution (Adr) Di Kawasan Asean - Delfiyanti (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
In order to realize the ASEAN single market, which is one of the free flows of capital or investments in the ASEAN region, on 26th of February 2009 in Cha-am, Thailand, the government delegations of ASEAN member countries signed the ASEAN Comprehensive Investment Agreement known by the abbreviation of ACIA Agreement. Indonesia has participated in signing the investment cooperation agreement in ASEAN. The implication that the ACIA Agreement bears towards Indonesia is the obligation to take measures to harmonize its investment regulations in accordance with the ACIA rules, especially the provisions contained in Law no. 25 of 2007 on Capital Investment. Apart from regulating investment cooperation agreements, the ACIA Agreement regulates the resolution of investment disputes between ASEAN member countries. Regarding the dispute resolution mechanism, the ACIA Agreement uses 2 channels, namely extra-legal channels (Alternative Dispute Resolution/ADR) and legal channels (Court/Arbitration). The choice of dispute resolution using this mechanism depends on the parties to the dispute. In this case, the choice of dispute resolution through the Alternative Dispute Resolution (ADR) mechanism also has separate regulations in this agreement. Furthermore, in Law no. 25 of 2007 on Capital Investment which applies in Indonesia also regulates the issue of resolving investment disputes in the form of Alternative Dispute Resolution (ADR). Therefore, the problems in this research are first, how is the implementation of the Alternative Dispute Resolution (ADR) mechanism in resolving investment disputes between ASEAN member countries and second, what are the challenges and efforts to implement the Alternative Dispute Resolution (ADR) mechanism in resolving investment disputes among ASEAN member countries, especially for Indonesia. This research uses a normative legal research method through document study, namely by conducting a literature search for materials or materials related to the Alternative Dispute Resolution (ADR) mechanism in resolving investment disputes based on applicable laws both internationally and nationally. The data used is secondary data through primary legal materials, secondary legal materials and tertiary legal materials.